Early detection and treatment of Speckled leukoplakia - Selviana Tampoma; Iwan Hernawan (Dental Journal (Majalah Kedokteran Gigi), 2016)
Background: Leukoplakia is one of potentially malignant disorders that can be found on oral mucosa. Speckled leukoplakia is a rare type of leukoplakia with a very high risk of premalignant growth. Approximately 3 % of worldwide population has suffered from leukoplakia, 5-25% of which tend to be malignant leukoplakia. Purpose: This case report was aimed to discuss about early detection of speckled leukoplakia as one of potentially malignant disorders. Case: A 62 year old male patient came with chief complaint of bald and painful tongue since one month ago. The patient has a history of allergic reaction, hypertension, uric acid, and hepatitis B. He had been a heavy smoker since young until 10 years ago. Intra oral examination showed a firm, rough, non scrapable white plaque lesion with a size of 1 x 1.5 cm, surrounded by painful erosion with diffuse boundary. Case Management: Based on cytology examination, the patient was reffered to oncologist to get an excisional biopsy. Next, the patient succesfully underwent the excisional biopsy and came for control. The results showed the healing process of the lesion with a minimal complaint of bald tongue, especially when eating spicy or hot meal. To improve healing process, the patient then was given an antibacterial mouth rinse containing zinc and mulvitamin. Conclusion: Speckled leukoplakia could show high malignant transformation rate, therefore, early detection and treatment are necessary.